Successful reading instruction - Kamil, Michael L.; Manning, JoAnn B.; Walberg, Herbert J., 1937- (Research in educational productivity., 2002)
A study of successful reading instruction. The articles cover topics such as the use of computer technology for reading instruction, and engagement and motivation in reading instruction. They are divided into two sections: "Reading Research and Assessment" and "Reading Instruction and Practice".